(untitled) (Bangladesh Journal of Pharmacology, 2016)
The main objective of the present study was to evaluate the antitumor and apoptotic effects of caryophyllene oxide in MG-63 human osteosarcoma cells. Cell viability of these cells was evaluated by MTT assay while as in vitro wound healing assay was used to study the effect of caryophyllene oxide on cell migration. Fluorescence microscopy and transmission electron microscopy were used to study the changes in cell morphology once the cells undergo apoptosis. Caryophyllene oxide significantly led to cytotoxicity in MG-63 cells showing dose-dependent as well as time-dependent effects. Caryophyllene oxide led to an inhibition of wound closure significantly. At caryophyllene oxide doses of 20, 80 and 120 µM, the percentage of cell migration was shown to be 94.2, 67.1 and 14.8% respectively. With an increase in the caryophyllene oxide dose, the extent of apoptosis also increased characterized by cellular shrinkage, membrane blebbing, chromatin condensation and apoptotic body formation. Video Clip of Methodology: Cell viability assay: 2 min 22 sec Full Screen Alternative